2018
DOI: 10.20944/preprints201804.0109.v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dissolved Gas Analysis Principle-Based Intelligent Approaches to Fault Diagnosis and Decision Making for Large Oil-Immersed Power Transformers: A Survey

Abstract: Compared with conventional methods of fault diagnosis for power transformers, which have defects such as imperfect encoding and too absolute encoding boundaries, this paper systematically discusses various intelligent approaches applied in fault diagnosis and decision making for large oil-immersed power transformers based on dissolved gas analysis (DGA), including expert system (EPS), artificial neural network (ANN), fuzzy theory, rough sets theory (RST), grey system theory (GST), swarm intelligence (SI) algor… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 80 publications
(123 reference statements)
0
5
0
Order By: Relevance
“…Hydrocarbon gases, such as methane and ethylene, are formed if the fault involves an oil-impregnated structure [7].…”
Section: Relationship Between Faults and Dissolved Gas Producedmentioning
confidence: 99%
See 2 more Smart Citations
“…Hydrocarbon gases, such as methane and ethylene, are formed if the fault involves an oil-impregnated structure [7].…”
Section: Relationship Between Faults and Dissolved Gas Producedmentioning
confidence: 99%
“…Large quantities of carbon dioxide and carbon monoxide are produced when thermal faults attack cellulose. Hydrocarbon gases, such as methane and ethylene, are formed if the fault involves an oil‐impregnated structure [7].…”
Section: Fault Types and Dgamentioning
confidence: 99%
See 1 more Smart Citation
“…4. According to GB/T 7252-2001 [28], the standard value of the onboard traction transformer C 2 H 4 in the normal state should be zero ppm. In Table 4, the content of C 2 H 4 significantly exceeds the standard, which further reflects the status change of the onboard traction transformer.…”
Section: ) Characteristics Of Dissolved Gases In Insulating Oilmentioning
confidence: 99%
“…It is demonstrated that fuzzy logic, metaheuristics, and ANN can provide improved performance in general engineering applications [ 19 , 20 , 21 , 22 , 23 ]. Specifically in transformer oil diagnoses, [ 24 ] introduces an intelligent approach used to diagnose the fault and to make the decision for oil-immersed power transformers, based on the DGA principle. In [ 25 ], a deep parallel detection technique for dissolved gas analysis of the transformer is used.…”
Section: Introductionmentioning
confidence: 99%